MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL KOOPERATIF THINK PAIR SHARE BERBANTUAN POWERPOINT DI SMP NEGERI 3 SUNGAI KAKAP - Sulistiyowati, Erni; Titin, Titin; Wahyuni, Eko Sri; Ningsih, Kurnia; Yuniarti, Anisyah (Jurnal Visi Ilmu Pendidikan, 2025)
This study aims to describe the learning implementation process and determine the improvement of student learning outcomes using the think pair share (TPS) model assisted by powerpoint. This research is a class action research conducted in two cycles with each cycle consisting of the stages of planning, action implementation, observation, and reflection. Data collection techniques through observation, documentation, and tests. The research subjects were VIIC class of SMP Negeri 3 Sungai Kakap totaling 32 students. The results showed that the percentage of learning process implementation in cycle I was 95.63% with a very good category and increased in cycle II by 98.75%. The learning outcomes of students in cycle I amounted to 78.13% with an average score of 81.88 and in cycle II to 87.50% with an average score of 87.03. Based on these results, the application of the TPS model assisted by powerpoint is able to improve the learning outcomes of students on the material of Indonesian ecology and biodiversity in class VIIC SMPN 3 Sungai Kakap.